2020
DOI: 10.1371/journal.ppat.1008877
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide transposon mutagenesis of paramyxoviruses reveals constraints on genomic plasticity

Abstract: The antigenic and genomic stability of paramyxoviruses remains a mystery. Here, we evaluate the genetic plasticity of Sendai virus (SeV) and mumps virus (MuV), sialic acid-using paramyxoviruses that infect mammals from two Paramyxoviridae subfamilies (Orthoparamyxovirinae and Rubulavirinae). We performed saturating whole-genome transposon insertional mutagenesis, and identified important commonalities: disordered regions in the N and P genes near the 3' genomic end were more tolerant to insertional disruptions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Whether this facilitates persistence and detection of biologically relevant variants or only the ones that are Vero-specific is unknown. Bamford et al [25] and Ikegame et al [18] that obtained results comparable to ours also used Vero as a cellular substrate. Still, it must be emphasized that a variety of factors, including innate immunity reactions, influence the variability of viral populations and the heterogeneities observed during passaging in Vero cells cannot be considered as general quasispecies characteristics of MuV strains.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Whether this facilitates persistence and detection of biologically relevant variants or only the ones that are Vero-specific is unknown. Bamford et al [25] and Ikegame et al [18] that obtained results comparable to ours also used Vero as a cellular substrate. Still, it must be emphasized that a variety of factors, including innate immunity reactions, influence the variability of viral populations and the heterogeneities observed during passaging in Vero cells cannot be considered as general quasispecies characteristics of MuV strains.…”
Section: Discussionsupporting
confidence: 82%
“…Heterogeneous sites we detected were in a nearby downstream region. Ikegame et al [18] also observed that recombinant MuVs preferentially permit mutations (which in their study were insertions) in N and P genes, especially in their noncoding regions. Whether changes in 5 terminal region of N gene can have influence on the nature or quantity of defective interfering particles as has been shown for a point mutation in Sendai virus [57]; or influence mRNA transcription gradient as in measles virus [58] has yet not been shown for any MuV strain.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations